2020
DOI: 10.1155/2020/6661691
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Diabetes Mellitus on Patients Undergoing Primary Total Lower Extremity Arthroplasty: A Systematic Review and Meta-Analysis

Abstract: Background. Diabetes mellitus (DM) is a common disease that has an adverse impact on most orthopedic surgeries, and its prevalence has gradually increased in recent years. We aim to investigate the influence of DM on comorbidities and complications of patients undergoing primary total lower extremity arthroplasty. Methods. PubMed, Embase, Cochrane Library, Medline, and Web of Science were systematically searched for relevant studies published before December 2019. Demographic data, comorbidities, and postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 61 publications
2
8
0
6
Order By: Relevance
“…DM is associated with immune system alterations, including impaired leukocyte function, impaired release of inflammatory cytokines in response to infection stimuli 26 and enhancing the formation of biofilm 27 . In our study, DM patients had a 1.6–2.0 times higher risk of SSC than non-DM patients, which was consistent with findings from other studies 28 , 29 . Notably, the risk was even higher in patients who had morning hyperglycemia 30 and poorly controlled hemoglobin A1c values 31 , indicating that the risk of SSC in DM patients would still be modifiable.…”
Section: Discussionsupporting
confidence: 93%
“…DM is associated with immune system alterations, including impaired leukocyte function, impaired release of inflammatory cytokines in response to infection stimuli 26 and enhancing the formation of biofilm 27 . In our study, DM patients had a 1.6–2.0 times higher risk of SSC than non-DM patients, which was consistent with findings from other studies 28 , 29 . Notably, the risk was even higher in patients who had morning hyperglycemia 30 and poorly controlled hemoglobin A1c values 31 , indicating that the risk of SSC in DM patients would still be modifiable.…”
Section: Discussionsupporting
confidence: 93%
“…Diabetic individuals had higher risks and prevalence of deep SSI (PJI) than non-diabetic patients, according to our findings. This finding is consistent with results published by Qin et colleagues in 2020, who found that patients with DM had a 1.76-fold greater risk of deep infection [37]. We believed that proper precautions should be taken when operating on diabetic patients for TKA, as previous research has shown that PJI is associated with extremely poor postoperative outcomes and a high mortality rate [22].…”
Section: Discussionsupporting
confidence: 91%
“…ЦД є основною причиною сліпоти, ниркової недостатності, інфаркту, інсульту й ампутації нижніх кінцівок, обумовлює ранню інвалідизацію та летальність внаслідок пізніх ускладнень [9]. Слід зазначити, що ЦД є поширеним серед пацієнтів, яким проводять тотальне ендопротезування нижніх кінцівок [10], його діагностують у понад 20% пацієнтів, яким проводиться ендопротезування, а стресова гіперглікемія, що не є діабетичною, може спостерігатися у більш ніж 50% пацієнтів, яким проводиться ендопротезування [11].…”
Section: The Role Of Dexmedetomidine In the Structure Of Anesthesia F...unclassified
“…(2021), пацієнти, які перенесли тотальну артропластику колінного суглоба та з високим рівнем передопераційного D-димеру, мають значний ризик розвитку післяопераційної венозної тромбоемболії [16]. Крім того, пацієнти з ЦД частіше страждають від супутніх захворювань і мають вищий ризик ускладнень при тотальному ендопротезуванні нижніх кінцівок порівняно з пацієнтами без ЦД [10].…”
Section: The Role Of Dexmedetomidine In the Structure Of Anesthesia F...unclassified
See 1 more Smart Citation